Human Existence as Caliph and Implementation of Islamic Education - Darwis Hude; Made Saihu (Randwick International of Education and Linguistics Science Journal, 2024)
This article aims to examine more deeply the essence of humanity in Islamic education. In its study, this paper uses the literature study method, namely studying human essence from primary sources of the Islamic religion such as the Al-Qur'an and the Hadith of the Prophet. Education that ignores the goals, functions, and tasks of human creation from the concept of Islamic education is a concrete form of distance from Islamic educational practices. This article concludes that human existence is a combination of physical elements and spiritual elements or between material elements and immaterial elements, the elements of body, mind and spirit are a unity that cannot be separated. Since the time of creation, humans have been equipped by God with the potential to be "knowledgeable" or "knowledgeable". The potential for science or knowledge is what then differentiates humans from other creatures. Because of this potential, he became a noble creature and had more value, so he was appointed caliph on earth. From an educational perspective, the Qur'an provides a picture that humans are pedagogical creatures, namely creatures who have the potential to be taught and educated, which in the context of this verse is symbolized by Allah's teaching to Adam about the names of all objects. Thus, education is a necessary process for humans to guide, direct and actualize the potential that exists in humans.